Linguistic Models, Acquisition Theories, and Learner Corpora: Morphological Productivity in SLA Research Exemplified by Complex Verbs in German. (13th April 2017) - Lüdeling, Anke; Hirschmann, Hagen; Shadrova, Anna
Abstract : The present study analyzes morphological productivity for complex verbs in second language acquisition by analyzing a corpus of German as a Foreign Language (GFL). It shows that advanced learners of GFL use prefix and particle verbs relatively frequently and productively but less so than native speakers do and discusses these findings in the light of different linguistic models and acquisition theories. It argues that corpus data must be evaluated against good models and that it is necessary to make the categorization decisions available as annotations.